Comparison of haemodynamic responses to dobutamine and salbutamol in cardiogenic shock after acute myocardial infarction. Issue 6309 (9th January 1982) - Fowler, M B; Timmis, A D; Crick, J P; Vincent, R; Chamberlain, D A
Abstract : Nine patients with critically reduced cardiac output after acute myocardial infarction underwent a single cross-over comparison of dobutamine and salbutamol to compare the haemodynamic effects of these drugs, which have, respectively, predominantly beta 1-adrenergic and beta 2-adrenergic agonist activity. The responses were used to select the more appropriate treatment for individual patients. Only relatively small responses were obtained: those with poorest baseline measurements tended to show the least effect. When the results from the series were averaged, dobutamine (250-750 microgram/min) caused a small but progressive increase in cardiac index (1.8 to 2.2 1/min/m2) throughout the dose range. Systemic blood pressure was not increased, and calculated systemic vascular resistance fell from 25 to 19 units. Heart rate rose from 107 to 118 beats/min and stroke index from 17 to 19 ml/beat/m2. Pulmonary artery end-diastolic pressure fell from 18 to 15 mm Hg. Salbutamol (10-40 microgram/min) produced a similar progressive increase in cardiac index, from 1.6 to 2.21/min/m2. Systemic blood pressure was not altered, and systemic vascular resistance fell from 25 to 20 units. Heart rate rose from 105 to 119 beats/min and stroke index from 16 to 19 ml/beat/m2. Pulmonary artery end-diastolic pressure did not fall. Dobutamine and salbutamol have closely similar haemodynamic effects when used in cardiogenic shock after acute myocardial infarction. Both drugs increase cardiac index but heart rate also rises, and the increase in stroke index is relatively small. Mean arterial pressure is altered little by either agent, but dobutamine (in contrast with dopamine) tends to reduce pulmonary artery end-diastolic pressure, which may be beneficial.